2012
DOI: 10.1097/sap.0b013e3182583eb9
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of Vascular Endothelial Cells and Adipose-Derived Stem Cells as a Source for Bone Engineering

Abstract: The interaction between vascular endothelial cells (VECs) and osteoblasts (OBs) is the focus of this recent research. Vascular endothelial cells secrete bone morphogenetic protein, which promotes OB differentiation and stimulates OBs and their precursor cells to secrete vascular endothelial growth factor. Vascular endothelial growth factor is important in angiogenesis and angiopoiesis. Cloning studies have shown that adipose-derived stem cells (ADSCs) have the potential to differentiate into fat, bone, cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…9,[11][12][13][14][15][16][17]22,29,[63][64][65][66][67] The main rationale behind the use of these supplements is to provide signaling proteins or enzymes to activate mineral production by MSCs. Previous in vitro 2D studies have shown that the direct coculture of MSCs with endothelial cells [36][37][38][39] or chondrocytes 68 can provide the necessary factors to induce early markers of osteogenic differentiation (ALP expression) without the need for these supplements. A recent 2D study found that indirect coculture of MSCs with osteocytes led to increased calcium deposition compared with MSCs cocultured with osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[11][12][13][14][15][16][17]22,29,[63][64][65][66][67] The main rationale behind the use of these supplements is to provide signaling proteins or enzymes to activate mineral production by MSCs. Previous in vitro 2D studies have shown that the direct coculture of MSCs with endothelial cells [36][37][38][39] or chondrocytes 68 can provide the necessary factors to induce early markers of osteogenic differentiation (ALP expression) without the need for these supplements. A recent 2D study found that indirect coculture of MSCs with osteocytes led to increased calcium deposition compared with MSCs cocultured with osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical location of MSCs and vascular endothelial cells suggests that these two cell types are in direct cell-cell interaction and experience juxtacrine or paracrine signaling within the stem cell niche during endochondral ossification. Previous in vitro studies have shown that direct coculture of MSCs or osteoblasts with endothelial cells can upregulate production of the early osteogenic marker ALP, [36][37][38][39] without the presence of osteogenic supplements. Other studies have investigated whether coculture of MSCs and endothelial cells can increase ALP production in three-dimensional (3D) polymer scaffolds 40,41 or 3D cellular aggregates, [42][43][44][45] but the majority of these studies were conducted in the presence of osteogenic growth supplements.…”
mentioning
confidence: 99%
“…In 3-D matrices, a number of studies using co-cultures of two lineages have been published, with cell lines from different sources (human and murine), including differentiated cells mixed with undifferentiated cells (MSCs or progenitors). Among the cell culture models used to develop these hybrid constructs, human umbilical vein endothelial cells (HUVEC) [22], human outgrowth endothelial cells (OEC) [23], human microcapillary endothelial cells [24] and endothelial progenitor cells from cord blood have been used for co-cultures with human bone-derived cells [25], osteoblast-like MG63 cells [26], primary human osteoblast cells [27], human osteoprogenitor cells from bone marrow [28], MSCs from adipose tissue [29] or bone marrow [30]. However, combining differentiated cells with undifferentiated cells arising from different sources (mouse, human) in co-culture assay does not mimic the physiological situation that occurs in a clinical situation of bone repair.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated functional relationships between endothelium and adjacent cell types [45][49], [50], [51]. Designing tissue assembly approaches that allow critical paracrine interactions is mandatory for achieving in vivo-like performance of engineered tissues.…”
Section: Resultsmentioning
confidence: 99%